2017
DOI: 10.3390/w9010047
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Microbiological Quality of Effluents from Different On-Site Wastewater Treatment Systems across Finland and Sweden

Abstract: Domestic wastewaters, which cannot be disposed through sewage networks, must be treated with different on-site treatment systems; these are usually commercial, small-scale treatment plants or built sand filters. These systems are usually maintained by the house's inhabitants. This study was achieved by analysing the chemical and microbiological data of 717 effluents collected in Finland and Sweden. There were inadequate reductions in 31% of phosphorus effluents, 22% of nitrogen effluents and 5% of biological o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 20 publications
(35 reference statements)
7
12
0
Order By: Relevance
“…Sand filters with or without a phosphorus-adsorbing layer have proven to be the most cost-effective and environmentally-friendly approaches if long-term use and renovation needs are considered [7,8]. It has been revealed [8][9][10], however, that the treatment efficiency of sand filters can be highly variable.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sand filters with or without a phosphorus-adsorbing layer have proven to be the most cost-effective and environmentally-friendly approaches if long-term use and renovation needs are considered [7,8]. It has been revealed [8][9][10], however, that the treatment efficiency of sand filters can be highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Sand filters with or without a phosphorus-adsorbing layer have proven to be the most cost-effective and environmentally-friendly approaches if long-term use and renovation needs are considered [7,8]. It has been revealed [8][9][10], however, that the treatment efficiency of sand filters can be highly variable. Studies of many different sand filters demonstrated that those filters with P-adsorbing media were better at reducing phosphorus and nitrogen than filters without any adsorbing media [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our wetland system shows similar efficiency in bacteria and nutrient reduction to other wastewater treatment systems [44,45]. However, natural wetland-systems are usually cheaper to build and maintain [46,47].…”
Section: Discussionmentioning
confidence: 93%